Halogen bond triggered aggregation induced emission in an iodinated cyanine dye for ultra sensitive detection of Ag nanoparticles in tap water and agricultural wastewater. Issue 43 (10th July 2018) - Abdelbar, Mostafa F.; El-Sheshtawy, Hamdy S.; Shoueir, Kamel R.; El-Mehasseb, Ibrahim; Ebeid, El-Zeiny M.; El-Kemary, Maged
Abstract : Based on AIE triggered by halogen bond (XB) formation, we established an ultrasensitive and selective sensor for picomolar detection of Ag nanoparticles (Ag NPs). Abstract : Aggregation induced emission (AIE) has emerged as a powerful method for sensing applications. Based on AIE triggered by halogen bond (XB) formation, an ultrasensitive and selective sensor for picomolar detection of Ag nanoparticles (Ag NPs) is reported. The dye (CyI ) has an iodine atom in its skeleton which functions as a halogen bond acceptor, and aggregates on the Ag NP plasmonic surfaces as a halogen bond donor or forms halogen bonds with the vacant π orbitals of silver ions (Ag + ). Formation of XB leads to fluorescence enhancement, which forms the basis of the Ag NPs or Ag + sensor. The sensor response is linearly dependent on the Ag NP concentration over the range 1.0–8.2 pM with an LOD of 6.21 pM ( σ = 3), while for Ag + it was linear over the 1.0–10 μM range (LOD = 2.36 μM). The sensor shows a remarkable sensitivity for Ag NPs (pM), compared to that for Ag + (μM). The sensor did not show any interference from different metal ions with 10-fold higher concentrations. This result indicates that the proposed sensor is inexpensive, simple, sensitive, and selective for the detection of Ag NPs in both tap and wastewater samples.